Pengaruh Tata Kelola dan Partisipasi Masyarakat Terhadap Efektifitas Pengelolaan Dana Desa di Desa Mattirobulu Kabupaten Bone - Nina Agustina; Herlina Sakawati; Anisa Fitri; Putri Dzakila Handayani; Dewi Sulfa Saguni (PT. Palem Edukasi Nusantara, 2025)
This study aims to determine the influence of governance and community participation on the effectiveness of village fund management in Mattirobulu Village, Bone Regency. The underlying problem is weak governance, which has a direct impact on the low level of community participation. Governance processes such as Musrenbangdes (Village Development Planning Meeting) are often carried out merely as a formality and not in accordance with regulations, so that community participation in planning is not optimally accommodated. This research is a quantitative study using a descriptive approach. Data were collected through observation, interviews, questionnaires, and documentation. The data analysis techniques used include instrument validity and reliability tests, descriptive statistical analysis, normality tests, and inferential statistical analysis. The results show that the coefficient of determination (R Square) for the governance and community participation variables is 0.772. This indicates that governance and community participation together are able to explain 77.2% of the variance in the effectiveness of village fund management in Mattirobulu Village, which can be categorized as strong. This means that good governance is inherently linked to meaningful community participation, and effective village fund management cannot be separated from sound governance systems and active community involvement.